Mineralizable N in some Malaysian rice soils - Yusop, Mohd Khanif; Rahimahbivi, O. H. (1988)
Mineralizable soil N is a very important N source in rice soils. In some cases more than 60% of the N requirement in an N fertilized rice crop is derived from soil N. A laboratory study was conducted to determine mineralizable (N) and mineralization constant (K) of 14 rice soils with varying soil properties under submerged condition. Soils were collected at the depth of 0-15cm and incubated for eight weeks. Ammonium N was extracted at 0,2,4,6 and 8 weeks and determined by steam distillation. The ammonium-N mineralized was used to calculate No and K. The No ranged between 20.0 to 154.1mg/kg which represented between 1.0% and 7.3% of the total N. The K values ranged between 0.11 to 0.72Wk-1. The mineralized N at a specified time can be determined by using No and K values. The calculated and the observed mineralized N were compared: the results showed good agreement between the two values. The No and K values were not significantly affected by the total N,organic C and C/N ratio,however there is a significant correlation between No and K (r=0.76).